2014
DOI: 10.1155/2014/509643
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness and Sustainability of the Sterilization Policy in China

Abstract: The aim of this paper is to examine the sterilization policy in China. First, several indices are used to measure the status of China’s markets and to determine effectiveness and sustainability of the sterilization policy and the possible impacts it may have induced. Second, within a microeconomic framework, we incorporate the housing price variable into the target loss function of the monetary authority to explore its financial capabilities and evaluate the effectiveness and sustainability of China’s steriliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…The second group of studies includes, among others, Chung et al (2014), Christensen (2004, Moreno (1996), Tagaki and Esaka, ( 2001), Ouyang and Rajan (2005). These studies…”
Section: Empirical Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…The second group of studies includes, among others, Chung et al (2014), Christensen (2004, Moreno (1996), Tagaki and Esaka, ( 2001), Ouyang and Rajan (2005). These studies…”
Section: Empirical Literaturementioning
confidence: 99%
“…used multi-equations models such as simultaneous equation models and Vector Autoregressive (VAR) Models. For example,Chung, et al (2014) used simultaneous equation model based on microeconomic framework to investigate sterilization coefficient in China and also the sustainability of the sterilization policy in the wake of China's gradual shift towards market-oriented policies and globalization, including high volume of foreign exchange reserves which constituted about 70 per cent of the Peoples Bank of China's total assets as at 2012. Using the 2 stage least squares method, the results of the study which estimated the 2 equations of NDA and NFA show −0.717 and −0.831, respectively.…”
mentioning
confidence: 99%
“…It concludes that the sterilization has been highly effective. However, another study for China by Chung et al (2014) examined the sterilization policy for the country. The empirical results showed that Chinese monetary authorities sterilized almost all of the effects of international capital inflows and increased foreign exchange reserves on the monetary base.…”
Section: Review Of Empirical Literaturementioning
confidence: 99%
“…The empirical model that guided this study is derived from the analytical framework outlined above. Specifying the monetary policy reaction function for the estimation of sterilization coefficient, the model we adopted is a modification from Chung et al (2014) and it is specified as follows:…”
Section: Empirical Model Specificationmentioning
confidence: 99%